THE INFLUENCE OF FINANCIAL LITERACY, FINANCIAL TECHNOLOGY, OVERCONFIDENCE, AND RISK PERCEPTION ON INVESTMENT DECISIONS OF ENTREPRENEURS IN THE F&B SECTOR IN SURABAYA - Marscelintan Vasthi Giarta; Rudi Pratono (Fakultas Ekonomi dan Bisnis Universitas Wijaya Putra, 2025)
This study analyzes the factors that affect entrepreneurial investment decisions in the food and beverage (F&B) sector in Surabaya, a city with stable economic growth and a promising market. Using a quantitative approach, data were collected through questionnaires from 150 MSME actors. Multiple linear regression analysis was used to test the effects of financial literacy, financial technology, overconfidence, and risk perception on investment decisions. The results show that financial literacy, financial technology, overconfidence, and risk perception have a positive and significant effect on the investment decisions of MSME actors in Surabaya.